1990
DOI: 10.1007/bf03259618
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to A Review of its Pharmacodynamic and Pharmacokinetic Properties, and Therapeutic Potential in Superficial and Systemic Mycoses

Abstract: Principles and practice of infectious diseases, 3rd ed. Churchill Livingston, New York, 1990 Halsted Cc. Rapid tests for group A streptococcus: unsettled issued. Infectious Diseases Newsletter 5: 83-84, 1986 Idsoe 0 , Guthe T, Wilcox RR, et al. Nature and extent of penicillin side reactions with particular reference to fatalities from anaphylactic shock. Bulletin of the World Health Organization 38: 159-188, 1968 Kaplan EL. The rapid identification of group A beta-hemolytic streptococci in the upper respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
316
2
17

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(350 citation statements)
references
References 0 publications
15
316
2
17
Order By: Relevance
“…This is in agreement with the observations of other investigators (16,28,32,37,38). Since protein binding is reported to be low for Flu (1,14,17), the effect of serum on its antifungal activity was not tested.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the observations of other investigators (16,28,32,37,38). Since protein binding is reported to be low for Flu (1,14,17), the effect of serum on its antifungal activity was not tested.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, there is a need for effective and less toxic drugs for the treatment of patients with these infections. One of these antifungal agents is the triazole fluconazole (Flu) (4,10,14,33,34,41). In vivo experimental studies suggested that Flu is active against disseminated candidiasis (8,9,29,31,32,35,37).…”
mentioning
confidence: 99%
“…An earlier study had found that plasma levels Ͻ250 ng/ml were associated with prophylaxis failure. 20 It takes an average of 14 days of itraconazole treatment before steady-state is reached 21 but the UK study of itraconazole solution found 76% of neutropenic adult patients had serum concentrations Ͼ250 ng/ml after 7 days and 84% reached these levels after 14 days. 22 This explains the importance of starting prophylaxis at least 7 days before the onset of neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…La asociación de tuberculosis con antiácidos, inhibidores H, AZT, 3TC, aciclovir vitamina C, culfato ferroso, ácidofólico fenitoína fluconazol diferentes tipos de micosis refleja mayor enfermedades de base y concomitantes como inmunosuoresión v mal estado aeneral del favorecedoras de la interacción. paciente; la enferkdad acidopéptica determina De los cinco pacientes con enfermedad el uso de fármacos cuya interacción sobre el acidopéptica, únicamente tres recibían trataitraconazol ha sido reconocida en otros estudios (3,9,16,(17)(18).…”
Section: Discussionunclassified
“…En los siete pacientes que recibieron rifampicina diarrea, que en casos severos pueden comprometer la administración y absorción del mismo fármaco. Es importante mencionar que aunque el itraconazol es mejor tolerado que el ketoconazol (13), los efectos gastrointestinales indeseables pueden también presentarse bajo terapia con este triazol (16).…”
Section: Discussionunclassified